Relatório de estágio técnico profissional em medicina veterinária: clínica médica e neurologia de pequenos animais - Palma, Valentina (2023)
The Professional Technical Internship (ETP) constitutes an essential stage for training in veterinary medicine, where it allows students to improve their knowledge both theoretical and practical. Enabling future professionals to understand the clinical routine and veterinarian job market. The ETP was carried out in the area of ​​Neurology and Small Animal Medical Clinic, under the guidance of Prof. Dr. Heloisa Helena de Alcantara Barcellos. It was carried out in two different locations, firstly in the Center Specialized in Veterinary Neurology, located in the Mont’Serra neighborhood, in Porto Alegre, from July 25th to August 31st, 2023, under the local guidance of the Doctor Veterinarian Kahena Morais, obtaining 217 hours and secondarily in the period of 01 September to October 16th at the Veterinary Hospital of the University of Passo Fundo, under local guidance from Veterinary Doctor Priscila Secchi, obtaining 267 hours at the Medical Clinic of Small Animals. Totaling 484 hours of ETP. Throughout the ETP period I had the opportunity to attend various clinical, specialist and surgical consultations, outpatient and emergency procedures, laboratory tests and imaging tests. In addition to monitoring hospitalized or critically ill patients. Through the tables was exposed to the monitored clinical case series, being subdivided by organic systems, local stage, species and diagnosis. Next, a case report of the approach will be described. diagnosis adopted in a canine with neurological signs resulting from distemper and associated canine neosporosis.